BLOOD ANTHOCYANIN LEVELS OF HEALTHY AND DIABETIC RATS AFTER FEED WITH A SINGLE DOSE OF PURPLE SWEET POTATO TUBERS AQUEOUS EXTRACT - Sutirta-Yasa, I W. P.; Jawi, and I M. (BALI MEDICAL JOURNAL; Vol 3 No 1 (2014), 2014)
Background: Aqueous extract of purple sweet potato tuber shown to decrease the blood glucose levels and has antioxidant properties in rats with streptozotocin-induced diabetes. The purpose of this study is to prove that an increase in anthocyanin levels in the blood of rats after administration of aqueous extract of purple sweet potato tubers in healthy and diabetic rats. Methods: This is an experimental study with randomized post-test only control group design. The subject of experiments were 72 rats, divided into two major groups, namely  diabetic rats (treatment group 36 rats) and control group (36 healthy rats). Each major group was divided into 6 small groups each 6 rats. The control group was given aqueous extract of purple sweet potato tuber with a dose of 4 ml single dose. The diabetic group were given streptozotocin and followed by aqueous extract of purple sweet potato tuber 4 ml single dose.  Observed variables include: blood glucose levels to define diabetes. To determine the levels of anthocyanin, the blood were taken and the level of anthocyanin were examination by HPLC method, in healthy  and diabetic rats after 30 min, 1 hours, 2 hours, 4 hours, 8 hours and 16 hours of giving single dose of aqueous extract of purple sweet potato tubers. Results: The results showed an increase in blood sugar levels were significant ( p < 0.05) in group given streptozotocin compared to control. Anthocyanin levels in the blood of two groups were significantly different from 30 min after administration of the extract to 8 hours after administration of the extract ( p < 0.05). Higher anthocyanin levels ( p < 0.05) was observed in control group (healthy rats) compared to rats with streptozotocin-induced diabetes. Peak levels of anthocyanin in blood were achieved after 2 hours of feeding. Conclusion: The conclusion of this study is the absorption of anthocyanin in aqueous extract of purple sweet potato tuber better in healthy rats compared to diabetic rats. The peak levels of anthocyanin was reached after 2 hours of aqueous extract of purple sweet potato tubers single dose consumption either in healthy rats and in diabetic rats.
Keywords: blood, glucose, anthocyanin, rats, diabetic.